Keberadaan Escherichia coli Extended Spectrum ?-lactamase Resistan Antibiotik di Peternakan Sapi Perah Cijeruk, Bogor - Pisestyani, Herwin; Lukman, Denny Widaya; Latif, Hadri; Sudarwanto, Mirnawati (Jurnal Veteriner; Vol 23 No 4 (2022)DO - 10.19087/jveteriner.2022.23.4.505, 2022)
Contamination of Extended spectrum-betha lactamase (ESBL) producing Escherichia coli in milk can cause public health problems. The misuse of antibiotics in dairy has implications for the emergence of multi-resistant bacteria that can infect humans through food (foodborne diseases). The ESBL producing E. coli is resistant to ?-lactam antibiotics (including penicillins and 3rd and 4th derivatives of cephalosporins). This study aimed to analyze the phenotype of antibioticresistant ESBL-producing E. coli from livestock, farmer, dairy cows, milk, and pasteurized milk. The research was conducted on a dairy farm in Cijeruk District, Bogor. The method used was the ESBL EC tricycle for phenotype confirmation consisting of culture on tryptone bile x-glucuronide (TBX) agar and MacConkey agar (MCA) with the addition of the cefotaxime antibiotic 4 µg/mL for the presumption of ESBL-producing E. coli followed by confirmation of ESBL producing E. coli with indol biochemical tests with sulfite indole motility (SIM) and double disk diffusion test (DDST) on Mueller Hinton agar (MHA). The results from this study showed that ESBL producing E. coli was not found in water, effluent, milker hand swabs, teat swabs, and milk from the individual cows. ESBL producing E. coli was identified from fresh milk (2/10) and pasteurized milk (2/10) on the same farm. ESBL-producing E. coli were resistant to eight antibiotics (ampicillin, cefotaxime, ceftazidime, cefpodoxime, cephalothin, streptomycin, azithromicyn, enrofloxacin). Multidrugresistant ESBL-producing E. coli is one of the foodborne diseases that pose a health threat to the community.